Policy Formulation to Reduce Deforestation in Riau Islands: A Review of Practices and Challenges - Gunawan, Rizky; Samin, Rumzi; Basalamah, Rezal Hadi (Future Science, 2024)
Various policies and programs have been issued by the Government of Indonesia to overcome climate damage caused by irresponsible individuals, such as PIPPIB, Indonesia FOLU (Forest and Other Land Use) Net Sink 2030, Climate Village Program, and various other pro-grams. Riau Islands Province is one of the provinces tasked with running the program. However, from various series of programs directed by the Ministry of Environment and Forestry of the Repub-lic of Indonesia, there are problems experienced such as Human Re-sources, Budget, and Inter-Island Connectivity that are difficult to reach. Therefore, this research aims to identify various policy op-tions that will be carried out by the Riau Islands Provincial Envi-ronment and Forestry Service in overcoming land damage or defor-estation that occurs. The research method used is a review study with data collection techniques in the form of documentation of var-ious related research results. The theory used is according to Thom-as R. Dye (2012) regarding the Process Model. The results showed that starting from the Problem Identification stage to Policy Imple-mentation, the Riau Islands Provincial Government used policy op-tions that had been prepared through the DLHK Riau Islands Strate-gic Plan, such as the Climate Village Program, Biodiversity Manage-ment (KEHATI), Forest Management, and several other programs. Until the Policy Evaluation stage, the government chooses policy options that are tailored to its fiscal and human resource capabili-ties and chooses policies that have been successfully implemented. One of the conclusions in this research is that there is a need for pol-icies and regulations in the implementation of activities that sup-port land damage control.